The Initial Speaking Ability of English Education Department Freshmen of Universitas Nasional Karangturi - Daud Jiwandono (English Education Department - Universitas Nasional Karangturi, 2021)
Future English teachers need to have excellent communication skills in English at all cost. One of the important skills to master is speaking because it often represents a teacher overall competence in the eye of the students. This research is aimed to identify the initial speaking ability of the future English teachers who were still in the first semester in their study. This study was designed using descriptive qualitative research method employing observation, questionnaires, students’ speaking assessment using IELTS speaking test format, as well as interview. The participants of this study were 8 freshmen of the English Education Department, Universitas Nasional Karangturi. The data analysis employed in this study was inductive analysis based on Burns (2010) and Hatch (2002). The results show that the majority of the students (75%) display low performance (basic user level) whereas only two of them (25%) had quite good results (independent user level). It was due to their lack of practice because they are still at the beginning stage in their English studies and have not been very mush exposed to natural English communication. Obviously, they need to have supportive environment to learn speaking and this is going to be a huge challenge for the lecturers in ensuring that by the time they graduate they have sufficient speaking competence to handle the teaching job. Second, based on the questionnaire, students do not think that their first language hinders their ability in learning English, rather, they are of the opinion that their experience in learning their first language actually helps them to learn English